Study of the prevalence of echinococcosis (hydatid cyst) in Kirkuk governorate for the period from 2016-2019 - Layla Abd-Al-Sattar Sadiq Laylani (Tikrit Journal of Pure Science)
The current study was conducted from April 19 to May 29, 2021  Public Health department, Animal Origin Division, in the Kirkuk Health department  in Kirkuk city to study the causes and spread of infections recorded for period from 2016-2019 in Kirkuk Governorate, 67 cases were diagnosed according to the months,. The highest infection recorded in 2019 was (26) 38.80% and the lowest infection was (10) 14.92% in each of 2016 and 2017 years. The group of health sectors showed the cyst disease caused by strays dogs, which is one of environmental pollutants, where Kirkuk First sector recorded the highest infection (31) 44.77%, while Hawija First sector recorded the lowest infection (4) 5.97%. The study recorded that the percentage of infection among females was 68.65%, and it was more than males 31.34%. The age group 15-25 years showed the highest number of injuries (46), with a rate of 68.65% of injuries during the years.